QF Q6.) Find the function for b.


The function notation f(x)=2x-4 means replace the x on the right-hand side with the value in parentheses on the left. For example, f(y)=2y-4; f(4)=2(4)-4=4; f(1)=2(1)-4=-2 and so on. The same principle applies to g(x), for example g(2)=4(2^2)-3=13, g(x+1)=4(x+1)^2-3=4(x^2+2x+1)-3=4x^2+8x+4-3=4x^2+8x+1 and so on. (g of f)(x) is another way to write g(f(x)), therefore g(f(x)) =g(2x-4)   [because f(x)=2x-4 =4(2x-4)^2-3 =4(4x^2-16x+16)-3 =16x^2-64x+64-3 =16x^2-64x+61

0 0

(g₀f)(x)=g(f(x)) =g(2x-4) =4(2x-4)^2-3 =4(4x^2-16x+16)-3 =16x^2-64x+61

0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers

More questions